Rubus laciniatus Willd. (Rosaceae), an introduced species new in the flora of Serbia and the Balkans - Krivošej Zoran; Prodanović Danijela; Preljević Nusret; Veljković Bojana (Botanica Serbica, 2018)
Rubus laciniatus has been found as a species new for the flora of Serbia during floristic investigation in the Ibar river valley. It was found on serpentine terrains near the town of Raška (SW Serbia). This is the single known locality of the given species on the Balkan Peninsula. Data on morphology, distribution, and habitat preferences of the species are provided, and the possible pathways of its introduction in Serbia are assessed